Perlindungan Hukum Bagi Para Nasabah Asuransi Pasca Terbentuknya Lembaga Penjamin Polis (LPP) - Malie, Adi Muliawansyah; Chumaida, Zahry Vandawati; Subagyono, Bambang Sugeng Ariadi (Universitas Medan Area, 2024)
This research aims to determine the legal certainty of the role of insurance supervisory institutions and the form of legal protection for insurance customers after the formation of the Policy Guarantee Institution (LPP). This has become urgent, considering that recently there have been many cases of failure to pay insurance claims to customers. This research method is normative, with an approach to statutory regulations and a conceptual approach. The sources of legal materials used are primary, secondary and tertiary legal materials. The method for collecting legal materials is carried out through literature study with the analysis method using analytical descriptive and systematic interpretation. The research results found that legal certainty regarding the role of insurance supervisory institutions is inherent in the Financial Services Authority (OJK) with its juridical basis being Law Number 21 of 2011 concerning the Financial Services Authority and Law Number 40 of 2014 concerning Insurance. OJK plays a role in risk mitigation and legal protection. The form of legal protection is preventive (prevention) and repressive (control). The policy guarantor is the authority of the Deposit Insurance Corporation (LPS). However, it is known that the minimum and maximum nominal limits of the policy guarantee that will be guaranteed are not regulated, thus indicating that legal certainty as well as legal protection for insurance customers has not been realized as it should be.